2016
DOI: 10.5018/economics-ejournal.ja.2016-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Transfer Costs Matter for Foreign Remittances? A Gravity Model Approach

Abstract: Using bilateral data on remittance flows to Pakistan for 23 major host countries, this is the first study that examines the effect of transaction costs on foreign remittances. The authors find that the effect of transaction costs on remittance flows is negative and significant; suggesting that a high cost will either refrain migrants from sending money back home or make them remit through informal channels. They also find that remittances are facilitated by the existence of migrant networks and improvements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Finally, the short‐ and long‐run impact of foreign remittance are positive on physical and human capital development. Ahmed and Martinez‐Zarzoso () analysed the impact of transaction costs on remittances to Pakistan. The study confirmed the negative relationship between the two variables; the remitter avoids formal sending if transaction costs are higher.…”
Section: Theoretical and Empirical Review Of Literaturementioning
confidence: 99%
“…Finally, the short‐ and long‐run impact of foreign remittance are positive on physical and human capital development. Ahmed and Martinez‐Zarzoso () analysed the impact of transaction costs on remittances to Pakistan. The study confirmed the negative relationship between the two variables; the remitter avoids formal sending if transaction costs are higher.…”
Section: Theoretical and Empirical Review Of Literaturementioning
confidence: 99%
“…Taking a different perspective, Ahmed and Martínez-Zarzoso (2016) and Kakhkharov et al (2017) focus on the cost of remitting for specific recipients, with data on remittances spanning the period from 2003 to 2013/2014. As expected, they find that transaction cost negatively affects the volume of remittances.…”
Section: Introductionmentioning
confidence: 99%
“…As the amount of remittances has an impact on the economy, the indicators that affect it, identified by Lianos (1997) are: the level of income of migrants, the inflation rate, exchange rate, the interest rate and the number of migrants. Also another factor of influence is the economic conditions in both countries (Ahmed & Mart ınez-Zarzoso, 2016). For instance, De Sousa and Duval (2010) studied remittances flows to Romania, in the period 2005-2009, that were received from various sending countries.…”
Section: Remittances and The Economic Growthmentioning
confidence: 99%